Krebs von den Lungen-6 glycoprotein circulating levels are not useful as prognostic marker in COVID-19 pneumonia: A large prospective cohort study - Castellví, Ivan; Castillo, Diego; Corominas, Hèctor; Mariscal, Anaís; Orozco, Sandra; Benito, Natividad; Pomar, Virginia; Baucells, Andrés; Mur, Isabel; de la Rosa-Carrillo, David; Lobo, David; Millan, Ana Milena; et al. (Frontiers in Medicine, 2022)
COVID- 19 has rapidly expanded worldwide. Currently, there are no biomarkers to predict respiratory worsening in patients with mild to moderate COVID-19 pneumonia. Small studies explored the use of Krebs von de Lungen-6 circulating serum levels (sKL-6) as prognostic biomarker of worsening of COVID-19 pneumonia. We aimed a large study to determine the prognostic value of sKL-6 in predicting evolving trends in COVID- 19. We prospectively analyzed the characteristics of 836 COVID- 19 patients with mild lung disease on admission. sKL-6 was obtained in all patients at least at baseline and compared among patients with or without respiratory worsening. The receiver operating characteristic curve was used to find the optimal cutoff level. One hundred and fifty-nine (19%) patients developed respiratory worsening during hospitalization. Baseline sKL-6 levels were not higher in patients who had respiratory worsening (median IQR 315.5 209-469 vs. 306 214-423 U/mL P=0.38). Last sKL-6 and the change between baseline and last sKL-6 were higher in the respiratory worsening group (p=0.02 and p<0.0001 respectively). The best sKL-6 cut-off point for respiratory worsening was 497 U/mL (area under the curve 0.52; 23% sensitivity, 85% specificity). sKL-6 was not found to be an independent predictor of respiratory worsening. A conditional inference tree (CTREE) was not useful to discriminate patients at risk of worsening. We found that sKL-6 had a low sensibility to predict respiratory worsening in patients with mild-moderate COVID-19 pneumonia and may not be of use to assess the risk of present respiratory worsening in inpatients with COVID-19 pneumonia.